Vascular endothelial growth factor C and D signaling pathways as potential targets for the treatment of neovascular age-related macular degeneration: a narrative review - Leitch, Ian; Gerometta, Michael; Eichenbaum, David; Finger, Robert P.; Steinle, Nathan C.; Baldwin, Megan E. (Ophthalmology and therapy, 2024)
The development of treatments targeting the vascular endothelial growth factor (VEGF) signaling pathways have traditionally been firstly investigated in oncology and then advanced into retinal disease indications. Members of the VEGF family of endogenous ligands and their respective receptors play a central role in vasculogenesis and angiogenesis during both development and physiological homeostasis. They can also play a pathogenic role in cancer and retinal diseases. Therapeutic approaches have mostly focused on targeting VEGF-A signaling; however, research has shown that VEGF-C and VEGF-D signaling pathways are also important to the disease pathogenesis of tumors and retinal diseases. This review highlights the important therapeutic advances and the remaining unmet need for improved therapies targeting additional mechanisms beyond VEGF-A. Additionally, it provides an overview of alternative VEGF-C and VEGF-D signaling involvement in both health and disease, highlighting their key contributions in the multifactorial pathophysiology of retinal disease including neovascular age-related macular degeneration (nAMD). Strategies for targeting VEGF-C/-D signaling pathways will also be reviewed, with an emphasis on agents currently being developed for the treatment of nAMD.